ANALISIS WACANA PEMBERITAAN MEDIA ONLINE KOMPAS. COM MENGENAI KASUS RAFAEL TRISAMBODO - Ginting, Teria S; Pohan, Syafruddin; Br Ginting, Siti Rahma (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
The problem to be studied in this research is how the discourse is developed in the online news of Rafael Trisambodo case. This research aims to describe the text structure (macro structure and microstructure, social cognition, and social context in online news discourse). The method used is descriptive qualitative with Van Dijk's critical discourse analysis model with reading and writing data collection techniques. Two strategies were carried out when analyzing the study data, namely identifying, clarifying, and interpreting the data. Researchers analyzed one trending news discourse, the Rafael Trisambodo case. Based on the findings of this study, it is known that the text illustrates the involvement of several discourse elements, namely semantic aspects, syntactic aspects, and lexicon stylistics. So that the description of the critical discourse analysis study is seen from the three discourse structures of Van Dijk's model and its elements regarding the text of the Rafael Trisambodo case. From the whole discourse critically analyzed in the online news text, the dialect in the news related to social cognition is used to influence and emphasize the Rafael Trisambodo case.